2018
DOI: 10.21276/obgyn.2018.5.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Huge fimbrial cyst causing bilateral hydroureteronephrosis - a rare case report

Abstract: Small fimbrial cysts are most commonly seen, sometimes become larger and presents with symptoms. Here we presents a case of huge fimbrial cyst detected incidentally in a 20 year nulligravida came to out patient department with abdominal distention. Examination and imaging revealed large abdominopelvic cystic mass with no solid areas or septations. Minilaparotomy done, right fimbrial cyst was evident, cyst wall removed intoto. Histopathology confirmed fimbrial origin. Paraovarian cyst should be included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…The majority of patients report no symptoms but the most common symptoms include lower abdominal pain and discomfort, menstrual irregularities, abdominal distension, and the pressure effects of a large cyst, torsion, or rupture [ 6 ]. Previously reported studies demonstrated that postmenopausal bleeding, dysmenorrhea or irregular menstruation, and intermittent lower abdominal pain have all been linked to fallopian tube teratomas [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients report no symptoms but the most common symptoms include lower abdominal pain and discomfort, menstrual irregularities, abdominal distension, and the pressure effects of a large cyst, torsion, or rupture [ 6 ]. Previously reported studies demonstrated that postmenopausal bleeding, dysmenorrhea or irregular menstruation, and intermittent lower abdominal pain have all been linked to fallopian tube teratomas [ 7 ].…”
Section: Discussionmentioning
confidence: 99%